2002
DOI: 10.1002/pon.608
|View full text |Cite
|
Sign up to set email alerts
|

Which cancer patient completes a psychosocial intervention program?

Abstract: The present study explored the similarities and differences in patterns of psychological distress, coping strategies and social support of 41 cancer patients who dropped out of a psychosocial therapy program and 20 patients who completed the program as agreed. The findings indicated that only depression, out of nine brief symptom inventory subscales, predicted which patients would complete the program, i.e. patients with a high level of depression tended to complete the psychosocial intervention program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…After screening for psychosocial dysfunction, 86% of the eligible participants were recruited to the intervention study, with a very low 3-month attrition rate of fewer than 10%. It is postulated that limiting the intervention to participants with known psychosocial distress may account for the high level of adherence with the intervention and this is in keeping with previous research [8,11], which found that those who comply with psychosocial interventions are usually in greater psychological distress. Furthermore, it may be suggested that because the study design was quasiexperimental in nature it permitted participants to 'selfselect' into the experimental or control group and this may also have contributed to high recruitment and completion rates.…”
Section: Discussionmentioning
confidence: 66%
“…After screening for psychosocial dysfunction, 86% of the eligible participants were recruited to the intervention study, with a very low 3-month attrition rate of fewer than 10%. It is postulated that limiting the intervention to participants with known psychosocial distress may account for the high level of adherence with the intervention and this is in keeping with previous research [8,11], which found that those who comply with psychosocial interventions are usually in greater psychological distress. Furthermore, it may be suggested that because the study design was quasiexperimental in nature it permitted participants to 'selfselect' into the experimental or control group and this may also have contributed to high recruitment and completion rates.…”
Section: Discussionmentioning
confidence: 66%
“…30 Another noteworthy finding is the extent to which perceived support from friends and family was a major theme differentiating between women who accepted the referral and those who did not. Although social support has not been found to predict completion of a psychosocial program, 31 it is a key predictor of psychological outcomes among patients with cancer 32 and their caregivers. 33 However, measures of distress, such as the DT, fail to take into account the amount and quality of the social support patients receive from their network.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have pointed out the dearth of non-European American samples and the typical low statistical power of research in this area 29. Other research has noted the high levels of drop-out associated with psychosocial interventions for cancer patients 30, 31. Such methodological shortcomings may bias estimates of treatment efficacy 26, 32.…”
Section: Interventions For Cancer Patientsmentioning
confidence: 99%